Neighborhood Crime Control in a Changing China: Tiao-Jie, Bang-Jiao, and Neighborhood Watches. (July 2017) - Messner, Steven F.; Zhang, Lening; Zhang, Sheldon X.; Gruner, Colin P.
Objectives: This research assesses the impacts of three distinctive crime control activities organized and directed by the neighborhood committees with the assistance of local police in contemporary urban China—Tiao-jie, Bang-jiao, and neighborhood watches. Tiao-jie deals with disputes and minor criminal cases. Bang-jiao provides guidance to residents who have committed minor offenses or have been released from correctional institutions to facilitate reintegration. Neighborhood watches engage local residents in crime prevention under the direction of neighborhood committees. Method: Using survey data recently collected in Tianjin, we examine the effects of indicators of the implementation of these neighborhood-based crime control strategies on residents' reports of household property victimizations that occurred within the neighborhoods with multilevel logistic regressions. Results: Net of a range of individual-level and neighborhood-level control variables, the indicators of the level of activity of Tiao-jie, Bang-jiao, and neighborhood watches exhibit negative effects on reported household property victimization. Conclusions: Our findings provide suggestive evidence that the traditional strategies of neighborhood-level crime control continue to be relevant in the China of today and that the role of collective efficacy appears to differ from that observed in Western cities.